Mathématiques
marevagrau03
45

résoudre les équations suivantes  (2x-1)(3x+1)=0   , (3x-2)(6x+5)=(3x-2)(2x+3)   ; (4x-1)²=(4x-1)(x+3)    ; (2x+1)²=(x+5)² SVP ;s

+4
(1) Réponses
Ahly1201

1) (2x-1)=0                                                (3x+1)=0 2x-1+1=1                                                3x+1-1=-1 2x=1                                                       3x=-1 2xsur2=1sur2                                           3xsur3=-1sur3 x=1sur2 =0.5                                             x=1sur3=0.3

Ajouter une réponse